المراقبة ما بعد البانوبتيك للدول العربية على مواقع التواصل الإجتماعي: مقاربة ما بعد بنيوية - حمايدية, اسماء (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تسعى هذه الدراسة إلى تسليط الضوء على الممارسات الأمنية الجديدة للدول العربية تجاه مواقع التواصل الاجتماعي، بالاعتماد على التكنولوجيا المعاصرة لمراقبة وضبط هذا الفضاء غير التقليدي ، خاصة بعد الدور الذي لعبه في تحفيز الانتفاضات العربية.وقد اعتمدنا في هذه الدراسة على ما قدمه التيار ما بعد البنيوي، وبالأخص إسهامات كل من "ميشال فوكو" و"جيل دولوز" وجهازيهما المفاهيمي، كأدوات تحليلية توفر لنا أطرًا تفسيرية جديدة لفهم الممارسات الأمنية للدول العربية عامة و مصر خاصةً، و محاولتها توظيف تكنلوجيا المراقبة والضبط، بأسلوب يتخطى المراقبة التقليدية "المكانية "، إلى مراقبة أكثر تعقيد وهي مراقبة البيانات داخل الحيز الرقمي، والتي تعرف بالمراقبة" مابعد البانوبتيك" . من أجل خلق مجتمع انضباطي جديد على هذا الفضاء الرقمي يسهل التحكم فيه والسيطرة عليه، منعا لتكرار استخدامه في تهديد أمن هذه الأنظمة. This study seeks to highlight the new security practices of Arab states towards social media that rely on contemporary technology to surveille and control this cyber space, especially after its role in stimulating Arab uprisings. In this study, we have relied on what the post-structuralist trend has supplied, particularly the contributions of "Michel Foucault" and" Gilles Deleuze" and their conceptual devices, as analytical tools that provide us with new explanatory frameworks to understand the security practices of Arab states. In this perspective, Arab states, and Egypt in particular, attempt to employ surveillance technologies in a manner that goes beyond "panoptic surveillance" leading to a more complex type of surveillance which is "dataveillance" within the "digital enclosure" known as "post panopticism". Such a policy aims to create a new disciplinary system that controls the social behavior in the digital space and attempts to prevent the repeated use of these platforms to threaten the security of those regimes